Perancangan Aplikasi Perbaikan Reduksi Salt Dan Pepper Noise Pada Citra Menggunakan Metode Discrete Wavelet Transform - Solly Aryza; Fitriani Damanik; Selly Annisa; Ayunajmita Ayunajmita (Universitas Islam Sumatera Utara, 2019)
Digital imagery may experience degradation or disruption. The noise in the digital image is called noise. A low-quality image caused by noise requires corrective measures to improve image quality without compromising more image detail quality. One of image improvement technique is image filtering method. The method that will be used in this final project to improve the image containing noise is Wavelet Transformation.The method will be applied to an image containing impulse noise (salt pepper). Wavelet transformation is a development of noise detection algorithm based on simple concept that if pixel belongs to uniform region, then it is near its color with neighboring pixel, hence uncorrected, if nothing close to neighboring pixel, then noise is detected then pixel value is replaced with value of the window being evaluated